Student perceptions of the importance of art content and activities in schools of general education and vocational schools in Croatia and Bosnia and Herzegovina - D. Drljača, Miroslav; Opić, Siniša; Matijević, Milan (Revija za elementarno izobraževanje, 2020)
The aim of research was to examine how students in higher secondary education estimate the importance of visual arts subjects for the acquisition of general knowledge and the importance of visual arts for their future profession. The participants (N=605) were students in the third year of higher secondary education. Although the participants in the sample did not attach importance to visual arts for their future professions, they assessed that during their education, activities that necessitated working with their hands helped them in developing their memorization skills and the ability to learn other subjects.
Keywords: visual arts; general education; educational neuroscience; educational sciences; brain development